Pemanfaatan Sertipikat Tanah Hasil Pendaftaran Tanah Sistematis Lengkap Untuk Peningkatan Modal Usaha Di Kabupaten Madiun - Andy Kurniawan; Mr Sudibyanung; Theresia Supriyanti (Tunas Agraria, 2020)
Land certificate as a result of Complete Systematic Land Registration Program (PTSL) provides an opportunity for the society, especially small and micro businesses to utilize it as assurance obtaining business capital. Sidorejo Village is one of the villages that became PTSL location in Madiun Regency in 2017 with total of 1,088 land parcels that had been certified. This study purpose to determine the utilization of business people who received PTSL certificates in order to increase business capital. This research is limited to 30 informants, using descriptive qualitative research methods to obtain an in-depth knowledge of the utilization of these business people then to know various obstacles encountered in obtaining loan funds. The results obtained are 16 business people who have used land certificates to obtain capital loans, but only 4 of these business people who have prospects of increasing business capital. While 14 other business people have not used it for any purpose on the grounds they still have enough capital and are afraid of not being able to pay installments every month.